Inside Medical Software: When Programming Errors Cost Lives. (19th May 2018) - Thimbleby, Harold
Abstract: Harold Thimbleby, See Change Digital Health Fellow at Swansea University, takes a look at computer error in the health sector, and considers the challenges faced in ensuring a change for the better.